Repeatability and agreement of visual acuity using the ETDRS number chart, landolt C chart, or ETDRS alphabet chart in eyes with or without sight-threatening diseases - Voraporn Chaikitmongkol (2018)
© 2018 American Medical Association. All rights reserved. IMPORTANCE The Early Treatment Diabetic Retinopathy Study (ETDRS) alphabet chart is not feasible for measuring best-corrected visual acuity (BCVA) for individuals who are unfamiliar with the Roman alphabet. The ETDRS Landolt C chart is an alternative, but it may not reflect true BCVA among those with confusion between left and right. The ETDRS number chart might overcome these limitations, but little is known regarding its reliability. OBJECTIVE To evaluate repeatability and agreement of BCVA using the ETDRS number chart or Landolt C chart compared with ETDRS alphabet charts in healthy and diseased eyes. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study was conducted in Thailand from July 1, 2015, to June 30, 2016, among 154 adult Thai individuals. Those who could read Roman alphabets were classified into the following 4 groups, using 1 eye per participant: group A, which comprised 60 healthy eyes (BCVA, 20/20-20/25); group B, which comprised 40 eyes with age-related cataract, diabetic macular edema, or age-related macular degeneration (BCVA, 20/20-20/40); group C, which comprised 40 eyes with age-related cataract, diabetic macular edema, or age-related macular degeneration (BCVA, 20/50-20/100); and group D, which comprised 14 eyes with age-related cataract, diabetic macular edema, or age-related macular degeneration (BCVA, 20/125-20/200). INTERVENTIONS Two standardized 4-m BCVA measurements with 3 different Precision Vision ETDRS charts (PV number, Landolt C, and alphabet), in random sequence, performed 30 minutes apart. MAIN OUTCOMES AND MEASURES Repeatability, agreement, and testing duration of BCVA. RESULTS Of 154 Thai participants (82 women and 72 men; mean [SD] age, 52.9 [18.2] years), the ETDRS number chart had strong repeatability coefficients (group A, 0.61 [95% CI, 0.42-0.75]; group B, 0.87 [95% CI, 0.78-0.93]; group C, 0.81 [95% CI, 0.67-0.90]; and group D, 0.81 [95% CI, 0.49-0.94]). Concordance correlation coefficients between the number and alphabet charts were also strong (group A, 0.89 [95% CI, 0.82-0.93]; group B, 0.97 [95% CI, 0.94-0.98]; group C, 0.92 [95% CI, 0.86-0.96]; and group D, 0.96 [95% CI, 0.87-0.99]), while the concordance correlation coefficients between the Landolt C and alphabet charts were lower (group A, 0.72 [95% CI, 0.52-0.83]; group B, 0.83 [95% CI, 0.68-0.91]; group C, 0.79 [95% CI, 0.61-0.89]; and group D, 0.89 [95% CI, 0.66-0.97]). The mean letter score difference between the number and alphabet charts was 1 (95% limits of agreement, -4 to +6) compared with -7 (95% limits of agreement, -18 to +5; P < .001) between the Landolt C and alphabet charts. CONCLUSIONS AND RELEVANCE The repeatability coefficients and concordance correlation coefficients suggest that ETDRS number charts are viable for measuring BCVA in clinical practice and trials for individuals who are unfamiliar with the Roman alphabet.